Konsepsi HAM Universial Dan Partikular Dalam Putusan Mahkamah Konstitusi - Sobirin Malian (Institut Agama Islam Negeri Metro, 2020)
The Constitutional Court's decision rejecting the petition for judicial review related to criminal articles for adultery and LGBT perpetrators in the Criminal Code can certainly reap the pros and cons. Because the Court'sdecision is a decision with a disenting opinion. Of the 9 judges, 5 judges thought the petition was unacceptable, while the other 4 judges thought the petition was acceptable. Therefore, this decision is interesting to study and analyze further from the point of view of law, psychology, religion and other sciences which have a correlation with the object of this decision. Theoretically, it is found that the concept of human rights (especially regarding LGBT) is not only related to the concept of universal human rights, there is also the concept of particular human rights, meaning that when discussing human rights issues, there are normative boundaries that are juridical, religious, and traditional / custom. Based on these universal and particular human rights concepts, it can be concluded that the correct decision by the Constitutional Court was to grant a request for a judicial review in relation to the criminal article for adultery and LGBT perpetrators.